Transient hypogammaglobulinaemia of infancy: many patients recover in adolescence and adulthood. (22nd July 2019) - Ameratunga, R; Ahn, Y; Steele, R; Woon, S-T
Summary: Transient hypogammaglobulinaemia of infancy (THI) is a relatively rare disorder where there is an exaggeration of the physiological nadir of immunoglobulin (Ig)G between loss of transplacentally acquired maternal IgG and production by the infant. Patients may be vulnerable to infections during the period of hypogammaglobulinaemia. The precise time to recovery in all infants is currently unknown. We sought to determine the clinical features and time–course of recovery for patients with THI. We reviewed our experience with THI over the last three decades in order to describe clinical and laboratory features, as well as the time–course of recovery. Forty-seven patients were identified with THI. Only thirty-seven per cent remitted by 4 years of age, while some patients did not recover until the third or fourth decade. In keeping with previous studies, the majority (25 of 47) presented with recurrent infections, nine had a family history of immunodeficiency and 13 had adverse reactions to food as their dominant clinical manifestation. Chronic tonsillitis developed in 10 patients and symptoms improved following surgery. The group with food allergies recovered sooner than those presenting with infections or with a family history immunodeficiency. Eight patients failed to respond to at least one routine childhood vaccine. Two have IgA deficiency and four individuals recovering in adolescence and adulthood continue to have borderline/low IgG levels. None have progressed to common variable immunodeficiency disorders (CVID). THI is a misnomer, as the majority do not recover in infancy. Recovery from THI can extend into adulthood. THI must be considered in the differential diagnosis of adolescents or young adults presenting with primary hypogammaglobulinemia. Graphical Abstract: